P021 Membrane TNF expression on monocytes and differentiation of monocytes into M2-M1 macrophages: 2 new biomarkers of rheumatoid arthritis. (21st February 2018) - Paoletti, A; Nocturne, G; Bitoun, S; Riviere, E; Pascaud, J; Ly, B; Mariette, X
Abstract : Introduction: Three monocyte subsets have been described based on their CD14 and CD16 expression profiles, the subpopulation CD14 + CD16 + being expanded in rheumatoid arthritis (RA) patients. Macrophages contribute in situ to the RA pathogenesis. They can display various states of activation or « polarisation ». Two distinct states of polarisation for macrophages have been recognised: the 'classically activated macrophage phenotype' (M1) and the 'alternatively activated macrophage phenotype' (M2). To sum-up, M1 are considered to be pro-inflammatory and M2 to be regulatory and anti-inflammatory. Objectives: Here, we have assessed monocytes subsets and their capacity of differentiation into M2 or M1 macrophages in RA patients and controls. Methods: PBMCs were isolated and we first determined monocytes subpopulations and looked at expression of membrane TNF (mTNF). After negative selection of monocytes, Macrophages were Derived from Monocytes(MDM) by 7 days of culture in the presence of M-CSF (M2 differentiation) or GM-CSF (M1 differentiation). Expression of total macrophages markers (CD11b and CD71) and the M2 macrophage polarisation markers (CD163 and CD206) were evaluated. Results: We have confirmed that the CD14 + CD16 + monocytes subset was expanded in RA patients. For the first time, we have demonstrated that mTNF expression was significantly increased only in monocytes in RA patients (CD14 + : Mean 5.6 % HD versus 10.6 % RA, CD14 + CD16 + : Mean 3.3 % HD versus 11.1 % RA, CD16 + : Mean 2.4 % HD versus 6.3 % RA). Moreover, mTNF expression on monocytes correlated with the activity of the disease assessed by DAS28 CRP (Spearman r 0.548 and p= 0.0021* ). We have observed a significant decrease of macrophages induction by M-CSF in RA patients as shown by a decreased expression of CD11b-CD71(Mean 87.2 % HD versus 57.1 % RA, P value **** ). Among MDM, we have found a specific decreased level of M2 markers (CD206 Mean 78.1 % HD versus 27 % RA and CD163 56.2 % HD versus 37.2 % RA) suggesting an impaired maturation to M2 stage in RA patients. Conclusions: Monocytes from RA patients have an increased expression of mTNF linked to activity of the diseases. RA patients have an impaired maturation of monocytes to M2 macrophages. This might suggest that RA monocytes have a propensity for preferential maturation towards a pro-inflammatory M1 phenotype thus contributing to synovial inflammation. Deeper characterisation of M1/M2 and effect of the different types of anti-TNF on this differentiation process are on-going and will be presented. Disclosure of interest: None declared